The adoption of IS/IT investment evaluation and benefits realization methodologies in service organizations: IT maturity paths and framework - Lin, Chad; Huang, Y.-A.; Cheng, M.-S. (Academy of Taiwan Information Systems Research, 2007)
This research examines the relationship between the levels of IT maturity and theuse of IS/IT investment evaluation and benefits realization methodologies via casestudies and survey in the service sector. The findings indicate that IT maturity has apositive impact on the adoption of IS/IT investment evaluation and benefits realizationapproaches. A major contribution of this research is the development of an IS/ITmaturity, investment evaluation and benefit realization methodologies matrix via the casestudies. The matrix can assist service organizations in making and substantiating betterbusiness decisions. The relationship between the level of IT maturity and the use of IS/ITinvestment evaluation and benefit realization methods has been further tested andvalidated in the subsequent survey.